Impact of Microwave Irradiation on the NO2 Gas Sensing Properties of ZnO Nanoparticles - Park, Jimyeong; Hwang, Jeong Yun; Shin, Jiyeon; Mirzaei, Ali; Roh, Jong Wook; Wang, Qingsong; Choi, Sun-Woo; Jin, Changhyun; Choi, Myung Sik (Korean Journal of Metals and Materials, 2025)
This study explores the influence of microwave (MW) irradiation time on the NO2 gas sensing performance of ZnO nanoparticles (NPs). ZnO NPs were subjected to MW irradiation for 1, 3, 5, and 7 minutes to assess the effects of defect engineering via MW irradiation on their sensing behavior. Phase and morphological characterizations using XRD and SEM confirmed that MW irradiation did not induce significant changes in the crystalline phase or surface morphology of the ZnO NPs. However, PL, XPS, TEM, and EDS results revealed the generation of defects, which were particularly pronounced after five minutes of MW exposure. The pristine ZnO NPs sensor displayed a response of 6.0 to 2 ppm NO2 at 250 °C. After five minutes of MW irradiation, the response nearly doubled to 11.25 under the same conditions and reached 34.63 at 10 ppm NO2. The improved sensitivity was attributed to the formation of defect sites, ZnO-ZnO homojunctions, and ZnO-Zn(OH)2 heterojunctions. Notably, the sensor irradiated for five minutes also demonstrated excellent selectivity toward NO2 in the presence of interfering gases. These results demonstrate that MW-assisted defect modulation is a promising and scalable strategy to boost sensing features of ZnO NPs. It is anticipated that high-efficiency sensors tailored for specific environmental and industrial applications could be developed with further optimization of MW parameters and integration with surface modification techniques.